PENGARUH PENGUNAAN METFORMIN TERHADAP MORTALITAS PASIEN COVID-19 DENGAN KOMORBIDITAS PENYAKIT DIABETES MELITUS: Systematic Review - Johannes Yulason Christyan Lubis (2022)
Background: COVID-19 is a global pandemic that causes many deaths. Mortality in COVID-19 is generally due to comorbid diseases. Diabetes mellitus is one of the comorbid diseases in COVID-19 that can cause death. Common therapy in COVID-19 patients with comorbid diabetes mellitus is metformin. However, there is debate regarding the use of metformin from various studies. This systematic review aims to analyze the effect of metformin use on mortality in COVID-19 patients with comorbid diabetes mellitus. Objective: to provide references related to relevant publications including summaries, data synthesis, and analysis of the effect of metformin use on mortality in COVID-19 patients with comorbid diabetes mellitus. Methods: Systematic Review conducted by searching literature from April to August 2021. The analyzed literature came from the PubMed and Google Scholar databases using the 2020 PRISMA-P flow chart. Results: The data obtained were from 27 kinds of literature discussing the effect of metformin use on mortality of COVID-19 patients with comorbid diabetes mellitus, 66.7% of the literature stated lower mortality in metformin users, 18.5% of the literature showed no significant difference, 11.1% of the literature stated that it did not affect mortality, and 3.7% of the literature. stated higher mortality in metformin users Conclusion: Metformin effect in controlling blood sugar levels, anti-inflammatory, antiviral so that it affects reducing mortality in COVID-19 patients with comorbid diabetes mellitus. Keywords: COVID-19, Diabetes Mellitus, Metformin, Mortality